Sign in
Please select an account to continue using cracku.in
↓ →
If p, q, r are 3 statements then $$ \sim(( \sim p \rightarrow q) \wedge (\sim p \rightarrow r))$$ is equivalent to
$$p \rightarrow(\sim q \rightarrow \sim r)$$
$$\sim p \wedge (q \rightarrow r)$$
$$\sim p \wedge (q \rightarrow \sim r)$$
$$\sim p \rightarrow (\sim q \rightarrow r)$$
Create a FREE account and get:
Terms of Service
CAT Formulas PDFCAT Syllabus PDFCAT Study Plan PDFCracku Brochure
Detailed syllabus & Topic-wise Weightage
By proceeding you agree to create your account
Free CAT Syllabus PDF will be sent to your email address soon !!!